Multiplex value cocreation in unique service exchanges - Razmdoost, Kamran; Alinaghian, Leila; Smyth, Hedley J. (Journal of Business Research, 2018)
While the temporal nature of value cocreation (i.e., the interdependencies between/among past, present, and future value cocreation) is acknowledged in the literature, the processes and mechanisms through which these interdependencies are deliberately managed (i.e., multiplex value cocreation) are not examined. Our study aims to unravel the “black box” of multiplex value cocreation by investigating the processes and mechanisms through which actors manage the temporal nature of value cocreation in unique service exchanges. The research design is a multiple case study comprising four firms engaged in the definition, design, and delivery of mega-infrastructure projects. Our results showed that multiplex value cocreation involves two core processes of institutional work and resource reconfiguration that are reciprocally interrelated, driven by actor motives and conflicts and facilitated by interaction mechanisms. We further propose that emerged institutions and existing previous similar service exchanges may eliminate the need for multiplex value cocreation in routine service exchanges.
Keywords: Value co-creation; Project; Service ecosystem; Service dominant logic; Temporal; Unique service